Biomechanical Evaluation of Cortical Bone Trajectory Fixation with Traditional Pedicle Screw in the Lumbar Spine: A Finite Element Study - Kuo-Chih Su (MDPI AG, 2021)
Cortical bone trajectory (CBT) is increasingly used in spinal surgery. Although there are many biomechanical studies, the biomechanical effect of CBT in combination with traditional pedicle screws is not detailed. Therefore, the purpose of this study was to investigate the effects of the traditional pedicle screw and CBT screw implantation on the lumbar spine using finite element methods. Based on the combination of the traditional pedicle screw and the CBT system implanted into the lumbar spine, four finite element spinal lumbar models were established. The models were given four different load conditions (flexion, extension, lateral bending, and axial rotation), and the deformation and stress distribution on the finite element model were observed. The results show that there was no significant difference in the structural stability of the lumbar spine model between the traditional pedicle screw system and the CBT system. In addition, CBT may reduce stress on the endplate. Different movements performed by the model may have significant biomechanical effects on the spine and screw system. Clinical spinal surgeons may also consider using the CBT system in revision spinal surgery, which may contribute to smaller wounds.